Characterization of Microsatellites in the Akebia trifoliata Genome and Their Transferability and Development of a Whole Set of Effective, Polymorphic, and Physically Mapped Simple Sequence Repeat Markers - Zhong, Shengfu; Chen, Wei; Yang, Huai; Shen, Jinliang; Ren, Tianheng; Li, Zhi; Tan, Feiquan; Luo, Peigao (Frontiers in Plant Science, 2022)
Akebia trifoliata is a perennial climbing woody liana plant with a high potential for commercial exploitation and theoretical research. Similarly, microsatellites (simple sequence repeats, SSRs) also have dual roles: as critical markers and as essential elements of the eukaryotic genome. To characterize the profile of SSRs and develop molecular markers, the high-quality assembled genome of A. trifoliata was used. Additionally, to determine the potential transferability of SSR loci, the genomes of Amborella trichopoda, Oryza sativa, Vitis vinifera, Arabidopsis thaliana, Papaver somniferum and Aquilegia coerulea were also used. We identified 434293 SSRs with abundant short repeats, such as 290868 (66.98%) single-nucleotide repeats (SNRs) and 113299 (26.09%) dinucleotide repeats (DNRs), in the A. trifoliata genome, 398728 (91.81%) of 344283 loci were physically mapped on the chromosomes, 35565 (8.19%) of 23486 loci were assigned to unassembled scaffolds, and a positive correlation (r = 0.98) was found between the number of SSRs and chromosomal length. Additionally, 342916 (99.60%) potential SSR markers could be designed from the 344283 physically mapped loci, while only 36160 could be viewed as high-polymorphism-potential (HPP) markers, findings that were validated by polymerase chain reaction. Finally, SSR loci exhibited broad potential transferability, particularly DNRs such as the ‘AT/AT’ and ‘AG/CT’ loci, among all angiosperms, a finding that was not related to the genetic divergence distance. Practically, we developed a whole set of effective, polymorphic, and physically anchored molecular markers and found that, evolutionarily, DNRs could be responsible for microsatellite origin and protecting gene function.